2003
DOI: 10.3109/2000-1967-114
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Pneumoniae Seropositivity in Patients with Cerebral Ischemic Attack with or without Silent Brain Infarcts

Abstract: We could not confirm a relation of C. pneumoniae seropositivity neither with SBI nor with acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Johnsen et al reported that the association between C. pneumoniae and cerebral stroke depends on sex and cutoff points for antibody titer(5),which was contradictory to our results that showed no significant association between antibody titers and sex. In the study of Sirmatel et al in 2003, no significant association was found between antibody against C.pneumoniae and cerebral stroke, which was similar to our findings (6). In a study in Cameroon, which assessed antibodies via with the aid of microimmunofluorescence assay, no association between IgG antibody and stroke was found; however, there was an association between IgA antibody and stroke.…”
Section: Discussionsupporting
confidence: 88%
“…Johnsen et al reported that the association between C. pneumoniae and cerebral stroke depends on sex and cutoff points for antibody titer(5),which was contradictory to our results that showed no significant association between antibody titers and sex. In the study of Sirmatel et al in 2003, no significant association was found between antibody against C.pneumoniae and cerebral stroke, which was similar to our findings (6). In a study in Cameroon, which assessed antibodies via with the aid of microimmunofluorescence assay, no association between IgG antibody and stroke was found; however, there was an association between IgA antibody and stroke.…”
Section: Discussionsupporting
confidence: 88%
“…Using microimmunofluorescence assay, we found that 94.3% of thrombotic stroke patients tested positive for IgA antibodies against C pneumoniae and 62.9% for IgG, similar to the high prevalence reported in studies from Japan, 20 Taiwan, 21 Israel, 22 United Kingdom, 23 and Turkey. 24 The seroprevalence of chronic C pneumoniae infection (IgA) was significantly higher in stroke patients than in the controls (OR, 4.29; 95% CI, 1.84 to 11.56; Pϭ0.0002 for all cases of stroke and OR, 21.0; 95% CI, 3.38 to 868.45; PϽ0.0001 for ischemic stroke). A possible limitation of our study is that not all cases had brain scans to distinguish the stroke type, and cardiac workup for cardioembolism was incomplete in the cases.…”
Section: Discussionmentioning
confidence: 98%
“…Cook [6,10,11]. In other studies CP infection was not associated with cerebrovascular disease [12,[14][15][16]. Kawashima and Kawada, Jahromni et al, Sirmatel et al and Heuschmann et al reported that they observed no association between CP infection and stroke.…”
Section: Discussionmentioning
confidence: 91%
“…Kawashima and Kawada demonstrated a significant elevation of CP-immunoglobulin (CP-IgG) in an ischemic stroke patient [12]. Since the association between antibodies against CP and CVA is yet controversial [13][14][15][16] and because, there are no studies examining the relation ship between the presence of CP antibodies level and CVA in Iran, we conducted this case-control study. The aim of the present study was to ascertain whether CP-IgG positivity was associated with ACI in hospitalized subjects.…”
Section: Introductionmentioning
confidence: 99%